CORRELATION BETWEEN THEORY OF CRIMINAL LIABILITY AND CRIMINAL PUNISHMENT TOWARD CORPORATION IN INDONESIA CRIMINAL JUSTICE PRACTICE - Septa Chandra (Jurnal Dinamika Hukum, 2017)
The question of the correlation between theory of criminal liability and criminal punishment on criminal acts committed corporation is important to investigate in order to provide justification for the criminal prosecution of corporations. How a mistake should be constructed from a corporation associated with the theory of corporate criminal liability. As a consequence of the improper condition on the corporate views of whether the corporation has made a criminal offense can be avoided as part of discretion in running the business. If these obligations are not met, the corporation can be condemned for committing crime. The practice of criminal justice to the determination of criminal liability for corporations is not fully in accordance with the theory of corporate criminal liability. In fact, the court decision does not yet reflect a consistent correlation between the theory of criminal liability and criminal punishment on criminal acts of the corporation.Keywords: criminal liability, corporate, criminal justice.